Influence of Rocks, Soils and Physiography in the Distribution of Swertia chirayita and Rubia cordifolia in Metamorphic Terrain of Kaski District, Western Nepal - Sharma, Ram Prasad; Das, A. K.; Raina, A. K. (Indian Forester, 2015)
A study was conducted to assess the influence of metamorphic rocks, soils and physiographic conditions on the growth and distribution of Swertia chirayita and Rubia cordifolia in Lotse Pakha and Bhakarjung community forests of Kaski district, Nepal for sustainable management. Biannual biophysical data and soil samples collection were conducted by establishing permanent sample plots of 2m x 5m for herb species. The study area contains dominantly the medium to coarse grained metamorphic rocks as phyllite and quartzite with numerous discontinuities. The interpretation of biophysical data indicated that the availability of MAPs vary with variation of altitude, slope, aspect, crown cover, rock types and soil properties. The frequency, relative frequency, density and relative density of S. chirayita and R. cordifolia were found to be medium to higher in the study area. The number of S. chirayita found to be higher in greater slope while R. cordifolia in lower slope. The species richness of these species shows higher within the altitudinal range 1700 - 2000 m. These species suitably grows in north-east aspect. The number of S. chirayita was found higher in 0-60 % crown cover but R. cordifolia has no significant trends. The physicochemical properties (soil pH, N, P, K, SOM and texture) of soil and weathered minerals resulted from metamorphic rocks in studied CFs favour the growth and distribution of these species.